(untitled) (REMUNOM, 2025)
Muruci is a fruit widely distributed throughout the Amazon region, and is also found in areas of the Northeast and Central-West of Brazil. It can be consumed both in natura and processed, used in the production of juice, creams, jellies, among others. This research aimed to characterize the physical- chemical and sensory parameters of industrialized muruci pulp jellies from three different manufacturers (A, B and C). The results obtained demonstrated that the jellies meet the quality standards, with variations in TSS and acidity. The sensory analysis showed high acceptability rates, above 70%, with Jelly A standing out in color and flavor, and Jelly C in texture and aroma. Regarding the gender of the participants, there was good acceptance, especially of Jelly C, followed by A. The absence of significant statistical differences between the groups indicates the market potential of muruci jellies for both genders. The interest in consumption, together with its nutritional and sensory qualities, positions muruci as a promising raw material for the food industry. The study emphasizes the relevance of products derived from the industrialized pulp of native fruits, such as muruci, helping to enhance national products and presenting new alternatives for the consumer market.